Internalisasi Nilai-Nilai Al-Maa’un ( الماعون ) Dalam Kerangka Pengembangan Kelembagaan Muhammadiyah Di Era Digital: Studi Tentang Pelayanan Jasa Berbasis Digitalisasi Pada Lembaga Amil Zakat Infaq dan Shadaqah Muhammadiyah (LAZISMU) Kabupaten Pameka - Hendri Masduki (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2020)
Al-Maa’un (الماعون) is the small part of organization Muhammadiyah dedication movement as the theological source reference to apply the holy Al-Qur’an values. The contextual Al-Maa’un (الماعون) values can be known by individual person of Amil (official person who collect the tithe) at Amil Zakat Infaq Institute and Muhammadiyah Shadaqah (LAZISMU) Pamekasan Regency with action or application form by the internal values of Al-Maun (الماعون) as the theological source reference to apply the holy Al-Qur’an values. The internal values of Al-Maun (الماعون) is manifested by proces of social construction of Amil at Amil Zakat Infaq Institute and Muhammadiyah Shadaqah (LAZISMU) Pamekasan Regency by three dialectical cases simultaneuosly containing of the external,the objectivity and the internal. The actions or applications is as the new identities for the Amil at Amil Zakat Infaq Institute and Muhammadiyah Shadaqah (LAZISMU) Pamekasan Regency in designing of Muhammadiyah institute management at digital period. Keywords:The Internal, Values of Al-Maa’un (الماعون), The Institution Development Muhammadiyah, The Meritoriuos Serve by Digital Form,The Amil Zakat Infaq Institute and Muhammadiyah Shadaqah (LAZISMU) Pamekasan Regency